Efforts To Improve Students’ Academic Performance Through Student Management During Blended Learning Implementation - Rizqi Nur Afifah (Universitas Negeri Jakarta, 2025)
This study aims to find out how to improve students' academic achievement during the implementation of blended learning in the era of the covid-19 pandemic. Blended learning has been implemented long before the COVID-19 pandemic. However, its implementation and implementation is not optimal. The beginning of the emergence of the pandemic made learning completely online. Currently, learning is slowly being carried out using blended learning, namely face-to-face and online. Online learning, which is used to be done at this time, has actually reduced students' academic achievement. In addition to declining academic achievement, students' motivation and interest in learning also decreased. This is because students feel bored with online learning that cannot meet face to face. The decline in academic achievement is also influenced by several factors including the lack of parental attention when students are learning, the internet network is not supportive, the learning environment is not conducive, the role of educators is less effective in managing the classroom, and the student management system is not good. Student management and collaboration and collaboration with parents are always applied in order to produce student outputs that are able to compete in global competition. The method used in this research is a qualitative method with a literature study approach. Sources of data obtained are secondary data sources, where the information obtained comes from books, journals, and others.